2020
DOI: 10.3389/fimmu.2020.00573
|View full text |Cite
|
Sign up to set email alerts
|

The Rules of Human T Cell Fate in vivo

Abstract: The processes governing lymphocyte fate (division, differentiation, and death), are typically assumed to be independent of cell age. This assumption has been challenged by a series of elegant studies which clearly show that, for murine cells in vitro, lymphocyte fate is age-dependent and that younger cells (i.e., cells which have recently divided) are less likely to divide or die. Here we investigate whether the same rules determine human T cell fate in vivo. We combined data from in vivo stable isotope labeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…with the explicit models showing good accuracy albeit with very wide credible intervals. However, upon widening the prior from [0, 1] to [0, 10] we found that the accuracy of the explicit kinetic heterogeneity models broke down resulting in very inaccurate estimates and extremely wide credible intervals (Fig. 7B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…with the explicit models showing good accuracy albeit with very wide credible intervals. However, upon widening the prior from [0, 1] to [0, 10] we found that the accuracy of the explicit kinetic heterogeneity models broke down resulting in very inaccurate estimates and extremely wide credible intervals (Fig. 7B).…”
Section: Resultsmentioning
confidence: 99%
“…The one exception to these priors is in Figure 7B where we explored the impact of prior assumptions. Here the prior distribution for p in the homogeneous model is [0, 10]. For the implicit heterogeneity model, priors are [0, 10] for p and d ∗ .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model is informed by, and the worked examples are for, data from in vitro experiments where stimulation is provided to a group of T or B cells, and the resulting proliferation occurs in a burst that can be followed by division tracking dyes or direct filming. Those population dynamics follows the pattern of an exponential rise, a period of division cessation, and then of cell loss that characterises immune responses in vivo ( Veiga-Fernandes et al, 2000 ; Costa Del Amo et al, 2020 ). As such, as with the original Cyton model ( Hawkins et al, 2007 ; Subramanian et al, 2008 ; Marchingo et al, 2014 ), Cyton2 can be successfully fit to in vivo data (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The temporal heterogeneity (TH) model assumed that each memory subset (T CM /T EM , host/donor) divides at its own uniform rate, but that Ki67 high cells, which are actively dividing or divided recently, are lost at a different rate to that of more quiescent Ki67 low cells. This is an instance of a more general model in which a cell's risk of death changes with the time since its last division [32]. Our TH model is itself a simple generalisation of a purely homogeneous model in which cells divide and die at constant, uniform rates, independent of their expression of Ki67.…”
Section: Modelling Brdu/ki67 Labelling Kinetics In Busulfan Chimeric ...mentioning
confidence: 99%